Dinamika Penghayat Ugamo Malim dalam Memperjuangkan Hak Sipil di Kabupaten Toba - Firmando, Harisan Boni; Simbolon, Elvri Teresia; Lumbantobing, Roida (Asketik: Jurnal Agama dan Perubahan Sosial, 2023)
The purpose of this study is to determine the dynamics of ugamo malim adherents in fighting civil rights. The research used qualitative methods through observation, documentation, and in-depth interviews with ugamo malim figures to understand the facts that exist in society. Furthermore, the researchers conducted data reduction before drawing conclusions. The results of the study show that people who adhere to ugamo malim are always faced with intolerance and discrimination. The incorrect understanding of the function and meaning of religion in life, including the views of the minority of ugamo malim adherents, makes it difficult for ugamo malim adherents to be accepted by the general public and government circles. The discriminatory actions felt by religious people from various regions in Indonesia united them in a social movement to gain official recognition from the state. Groups of adherents from various regions in Indonesia submitted a request for judicial review to the Constitutional Court (MK) and it was granted. The efforts of followers of ugamo malim to continue to exist and preserve the values and traditions of the Toba Batak people in social movement theory are called new social movements. The main and first social movement carried out by the ugamo malim community was marhamalimon. Through marhamalimons, various rituals were established, a new center of worship was established, and the organizational structure of the parmalim was also determined. Efforts to fight civil rights were also carried out by ugamo Malim through education. Various negative prejudices against ugamo malim people have been identified by various achievements in the field of education. Ugamo malim people have worked in many government and private institutions and occupy strategic positions.